STRUCTURAL TIME SERIES ANALYSIS AND FORECASTING FISH AND TIGER SHRIMP SEED COLLECTION FROM TWO TIDAL ESTUARIES IN SUNDARBANS - GOSWAMI, K. K.; BHAUMIK, U.; MUKHOPADHYAY, M. K.; SHRIVASTAVA, N. P.; SHARMA, A. P. (Journal of the Inland Fisheries Society of India, 2020)
Tidal estuaries in and around the Sundarbans in South 24 Parganas district of West Bengal are natural sources of fin and shell fish seeds. In this context, Structural Time Series Models (STSM) were developed to forecast daily fish seed collection fromdata generated under intensive study conducted in two tidal estuarine rivers of Sunderbans during the period 1994 to 1998.The trend plus cyclical models were used to estimate lunar effect, trend and seasonality from daily collection data and alsofor forecasting future values (R2 value are 0.82 and 0.87) of fish seed and Tiger shrimp seed collection (R2 value from 0.66 and0.89). All the components of the models were found to be significant and both cycles were stationary and representedseasonality or lunar effect.Key words: Structural Time Series Model, trend, cycles, forecasting, Sundarbans